O DEUS DE SARAMAGO Uma análise teopoética das obras Caim e O Evangelho Segundo Jesus Cristo. - Castro, Vera Lúcia de (2014)
The literary work of José Saramago, in deconstructing the idea of God, may show a non-institutionalized God, with deeper, more sensible, authentic characteristics. The hypothesis presented in this study is about the possibility of finding in this Portuguese author, aspects of a rich theology not easily found in theological works of dogmatic or systematic character which explicitly aims at revealing God. In this view, the writer would be a prophet, since he is the one that goes against society s predominant contemporary thought. Saramago s work, therefore, can be recognized as a prophetic voice in today s world. This study intends to establish a relationship between theology and literature in José Saramago s work. Reference is made especially to his novels: The Evangelho Segundo Jesus Christo and Cain. Based on Paul Tillich s theology of culture, this study intends to show that Saramago s work, in asserting his atheism, contributes to the affirmation of a thoughtful faith.